New Insights on the Emplacement Kinematics of the Seymareh Landslide (Zagros Mts., Iran) Through a Novel Spatial Statistical Approach - Rouhi, Javad; Delchiaro, Michele; Della Seta, Marta; Martino, Salvatore (Frontiers in Earth Science, 2022)
The giant prehistoric Seymareh landslide in the Zagros Mountains (Iran) is one of the largest known landslides on the Earth's surface. The debris with an estimated volume of 44 km3 dammed two rivers, generating three lakes, that persisted for about 3 ka after the event. The post overflow morphodynamics, characterized by an accelerated and intense stream network erosion, obliterated most of the primary landforms, such as ridges and blocks on the debris surface, making difficult for scientists to interpret the emplacement kinematics of the landslide. In this regard, a novel spatial statistical approach is proposed here to zonate the landslide debris in primary (original) and secondary (modified) regions which are respectively attributed to the original shape of the landslide debris and to the one reshaped by fluvial erosion. The zonal computation combines the density classes of the mapped primary (ridge and blocks) and secondary (gullies) landforms, according to assumed conditions for representativeness of primary and secondary zones. For validating the model, 62 soil samples taken from the debris surface were classified according to USCS standard and field density measurements were performed in 28 sites. Based on the classification results, 6 types of soils were detected among which 68% of them were ML. The ML samples were aggregated into 5 subgroups based on their relative proximity and for each subgroup, 4 permeability tests were performed. The permeability results demonstrate that the high permeability values are associated to secondary zones while low values to primary ones, thus confirming the zonation proposed by the statistical approach. The study of the spatial arrangement of the kinematic evidence on the primary landforms allowed to deduce that the landslide was a double-step single event, which infilled a paleovalley enclosed by two anticline folds. During the emplacement, a part of the debris dissipated its energy over passing the anticlines with divergent directions, NW, and NE, while the rest swept back into the Seymareh paleovalley into SE direction. The proposed approach represents a promising tool for detection of primary landforms to assess the emplacement kinematics of landslides.